Manajemen laba model jones dimodifikasi dan arus kas operasi terhadap keputusan investasi pada sektor aneka industri di BEI setelah implementasi IFRS - Alik Katur Rofiah, Binti; Pujiono, Pujiono (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this examination was to the benefits of accounting information in the form of earnings management and operating cash flow on investment decisions. One of the benchmarks in the consideration of investment decisions is the value of the enterprise which can be seen in its share price. The category of research used is quantitative using secondary data in the form of pool data. Companies used as research objects are in the different industrial sectors listed on the IDX after the implementation of IFRS. The data needed are financial statement data and company stock price data by using research is multiple linear regression. After testing the hypothesis, it shows that earnings management has no effect on the company's stock price, but operating cash flow affects the company's stock price. It shows that the financial statement information is useful for investors. This research suggests that further research should use companies whose data variance is not too high and classify companies that have positive and negative earnings management values so that results can be more informative in making an investment determination.